Turbo-coded adaptive modulation versus space-time trellis codes for transmission over dispersive channels. - Liew, T.H (IEEE Transactions on wireless communications)
Decision feedback equalizer (DFE)-aided turbo-coded wideband adaptive quadrature amplitude modulation (AQAM) is proposed, which is capable of combating the temporal channel quality variation of fading channels. A procedure is suggested for determining the AQAM switching thresholds and the specific turbo-coding rates capable of maintaining the target bit-error rate while aiming for achieving a highly effective bits per symbol throughput. As a design alternative, we also employ multiple-input/multiple-output DFE-aided space-time trellis codes, which benefit from transmit diversity and hence reduce the temporal channel quality fluctuations. The performance of both systems is characterized and compared when communicating over the COST 207 typical urban wideband fading channel. It was found that the turbo-coded AQAM scheme outperforms the two-transmitter space-time trellis coded system employing two receivers; although, its performance is inferior to the space-time trellis coded arrangement employing three receivers.